2022
DOI: 10.1007/s00395-022-00965-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-responsiveness to cardioprotection by ischaemic preconditioning in Ossabaw minipigs with genetic predisposition to, but without the phenotype of the metabolic syndrome

Abstract: The translation of successful preclinical and clinical proof-of-concept studies on cardioprotection to the benefit of patients with reperfused acute myocardial infarction has been difficult so far. This difficulty has been attributed to confounders which patients with myocardial infarction typically have but experimental animals usually not have. The metabolic syndrome is a typical confounder. We hypothesised that there may also be a genuine non-responsiveness to cardioprotection and used Ossabaw minipigs whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 94 publications
0
20
0
1
Order By: Relevance
“…injections. One explanation may lie in the distinct genetic backgrounds of the utilized strains, as several studies have consistently demonstrated that lineage-specific effects determine the susceptibility of experimental animal models to cardiotoxicity as well as cardioprotection [ 3 , 22 , 25 , 26 ]. Nonetheless, both acute models, utilizing a single high dose, and chronic models, employing repetitive injections of small doses, have been widely used to study AICM in mice [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…injections. One explanation may lie in the distinct genetic backgrounds of the utilized strains, as several studies have consistently demonstrated that lineage-specific effects determine the susceptibility of experimental animal models to cardiotoxicity as well as cardioprotection [ 3 , 22 , 25 , 26 ]. Nonetheless, both acute models, utilizing a single high dose, and chronic models, employing repetitive injections of small doses, have been widely used to study AICM in mice [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preparations, models and protocols which did not result in infarct size reduction were discarded and most often not reported. Only recently, with the recognition of the translational gap, have studies in rats 73,74 and pigs 75,76 reported failure of infarct size reduction by ischaemic conditioning. 77 Primordial non-responsiveness to cardioprotection by a given intervention, which is possibly determined by the genome, has been neglected so far and may account for some of the translational gap.…”
Section: Waiting For a Third Wave Of Cardioprotection – Understanding...mentioning
confidence: 99%
“…A recent study in Ossabaw minipigs which are prone to develop a full metabolic syndrome, including insulin resistance with progression to type 2 diabetes, hyperlipidemia, obesity, and hypertension with the subsequent development of coronary atherosclerosis and occasional spontaneous myocardial infarction, demonstrated loss of protection by ischemic PreC in these pigs even before they had developed the diseased phenotype; the loss of protection was associated with lack of activation of STAT3 and a primordial genetic difference in mitochondrial function and STAT signaling from other pig strains. Thus, lack of cardioprotection can even become manifest before a metabolic syndrome has developed ( Kleinbongard et al, 2022 ).…”
Section: Effects Of Nonmodifiable Risk Factors and Comorbidities On I...mentioning
confidence: 99%